Feminist Identity in Relation to Non-Suicidal Self Injury and Body Dissatisfaction - Johnson, Katie (My University, 2013)
Non-suicidal self-injury (e.g., intentional destruction of body tissue without suicidal intent; NSSI) is a growing problem, and is quite prevalent among college females (Whitlock et al., 2012). Objectification theory proposes that sociocultural pressures and objectification of women's bodies cause women to self-objectify, adopting an outsider's view of themselves (Fredrickson & Roberts, 1997). There is evidence that feminism may provide some protection against body dissatisfaction and disordered eating, perhaps because feminism empowers women to reject oppressive social messages, assert their opinions, and voice their desires (Chrisler 2011). The purpose of this study was to examine the relationships between feminist identity, perceived social pressures, selfobjectification tendencies, and both NSSI and body dissatisfaction.
Color poster with text, charts, tables, and graphs.
Keywords: Feminism; Non-suicidal self injury; Self image; Posters; Objectification theory